Distraction by unexpected sounds: comparing response repetition and response switching - García-López, Elena; Parmentier, Fabrice B. R. (Frontiers in Psychology, 2024)
Numerous studies using oddball tasks have shown that unexpected sounds presented in a predictable or repeated sequence (deviant vs standard sounds) capture attention and negatively impact ongoing behavioral performance. Here, we examine an aspect of this effect that has gone relatively unnoticed: the impact of deviant sounds is stronger for response repetitions than for response switches. Our approach was two-fold. First, we carried out a simulation to estimate the likelihood that stimuli sequences used in past work may not have used balanced proportions of response repetition and switch trials. More specifically, we sought to determine whether the larger distraction effect for response repetitions may have reflected a rarer, and thereby more surprising, occurrence of such trials. To do so, we simulated 10,000 stimuli sets for a 2-AFC task with a proportion of deviant trial of .1 or .16. Second, we carried out a 2-AFC oddball task in which participants judged the duration of a tone (short vs long). We carefully controlled the sequence of stimuli to ensure to balance the proportions of response repetitions and response switches across the standard and deviant conditions. The results of the stimuli simulation showed that, contrary to our concerns, response switches were more likely than response repetitions when left uncontrolled for. This suggests that the larger distraction found for response repetition in past work may in fact have been underestimated. In the tone duration judgment task, the results showed a large impact of the response type on distraction as measured by response times: Deviants sounds significantly delayed response repetitions but notably accelerated switches. These findings suggest that deviant sound hinder response repetition and encourage or bias the cognitive system towards a change of responses. We discuss these findings in relation to the adaptive nature of the involuntary detection of unexpected stimuli and in relation to the notion of partial repetition costs. We argue that results are in line with the binding account as well as with the signaling theory.